Closer to freedom : enslaved women and everyday resistance in the plantation South - Camp, Stephanie M. H. (Gender & American culture., 2004)
Recent scholarship on slavery has explored the lives of enslaved people beyond the watchful eye of their masters. Building on this work and the study of space, social relations, gender, and power in the Old South, Stephanie Camp examines the everyday containment and movement of enslaved men and, especially, enslaved women.